Mustelus fasciatus, Striped Smoothhound - Pollom, R. (2020)
The Striped Smoothhound (Mustelus fasciatus) is a medium-sized (to 177 cm total length) shark that occurs in the Southwest Atlantic from Santa Catarina, Brazil, to southern Buenos Aires Province, Argentina. It is demersal on the continental shelf and upper slope, from inshore to 500 m depth. It is captured in intense and largely unmanaged commercial and artisanal demersal trawl, gillnet, and beach seine fisheries throughout its range. There are two population reduction estimates from research trawl surveys: (1) the southern Brazilian shelf; and, (2) the Argentina-Uruguay Common Fishing Zone. First, on the southern Brazilian shelf, catches of adults in research trawl surveys declined by 95% between 1981 and 2005, equivalent to a >99% population reduction over three generation lengths (43.5 years). Second, in the coastal region of the Bonaerensean District of northern Argentina and Uruguay, the biomass of this shark in trawl surveys decreased by 96% between 1994 and 1999, also equivalent to a >99% reduction over three generations. Due to the level of intense and largely unmanaged fishing pressure across its range, combined with its relatively unproductive life history, and noted declines, it is suspected that the Striped Smoothhound has undergone a population reduction of >80% over the past three generations (43.5 years), and it is assessed as Critically Endangered A2bd.